Assessment of the impact of interference signals on the decision circuit of the receiving-analyzing route of digital radio engineering systems - V. E. Emelyanov; S. P. Matyiuk (Научный вестник МГТУ ГА, 2022)
Currently, due to the increasing complexity of navigation support for aircraft (A/C), with the growth of requirements for them, it is increasingly necessary to develop systems for integrated processing of navigation information. The facilities for radio engineering flights support and aeronautical telecommunications are the main source of collecting processing and presenting information about the air situation to the traffic control staff. They are also used to solve the number of navigation problems. At the same time, the level of flight safety, along with the capacity of air traffic control zones depending on the decision of the ATC unit, is largely specified by the reliability of the various input information provided. At another point, most sophisticated digital tools for radio engineering flights support and aeronautical telecommunications at the output of the receiving-analyzing route have a decision or threshold circuit, the actuation of which, as a result of exposure to a mixture of noise and interference signals, reduces the reliability of information due to bursts of signal distribution, provided that impulse interference affecting the equipment and mush of receivers are not correlated. The work provides an estimate of the average amount of signal bursts at the output of the decision circuit taking into consideration the analysis of the probabilistic characteristics of the signals under consideration. For noises subject to the Rayleigh distribution and narrow-band impulse interference with a zero-mean value, the mathematical expectations of the average response time and the average number of positive bursts of the estimated process are found. The case of interfacing two airway surveillance radars “Skala-M” and “ATCR-22”, which have virtually identical operating characteristics, is analyzed. The dependence of the burst duration is calculated for the situation when the “Skala-M” radar is a source of unintended EMI for the “ATCR-22” radar.